The study of cutaneous malignancies at a tertiary care hospital in central india - Saldanha, Elroy; Dhakad, Vinod; Patel, Dhruv; Mehta, Nikhil; Ahmed, Zeeshanuddin; Jain, Amar; Desai, Sanjay (International Journal of Research in Medical Sciences, 2019)
Background: There has been an alarming rise in the incidence of various diseases including that of cancer in the world with increase in the incidence of cutaneous malignancies owing to various changes that have taken place in the society over the past few years with respect to the culture, the lifestyle and also a contributory role has been played by the changes in the atmosphere as a result of increase in the air pollutants in the environment. Based on the scenario, we decided to conduct a study to evaluate the presentation and the management cutaneous malignancies in a teaching hospital set up in central india. Methods: A retrospective study was conducted between the time period of 1 year on the records of patients who were diagnosed with cutaneous and related malignancies who were treated at our Institute on a predesigned semi structured performa. SPSS version 23.0 was used for the analysis of the data collected. Results: We evaluated a total of 29 cases, Squamous cell carcinoma (SCC) was the most common histological type (51.72%) followed by melanoma (27.59%) and basal cell carcinoma (BCC, 20.69%). 75.86% of patients with cutaneous malignancies were males and 24.14% were females. Mortality rate observed was 13.7%. Conclusions: The most common cutaneous malignancy seen in this study was squamous cell carcinoma having increased propensity towards males than females. Rate of loco-regional disease and median disease-free survival is directly dependent on the adequacy of disease-free surgical margin and to the limited extent on the adjuvant therapy.